STUDY OF THE EMOTIONAL STATUS OF PATIENTS WITH ACUTE MYOCARDIAL INFARCTION AND THEIR RELATIVES AT DIFFERENT STAGES OF THE PATIENT'S ROUTE - Holovanova, I.A.; Oksak, G.A.; Filatova, O.V.; Lyakhova, N.O.; Pluzhnikova, T.V.; Khorosh, M.V.; Filatova, V.L. (World of Medicine and Biology, 2022)
It is difficult for a person with any disease to control their emotions, it is difficult to understand their emotional experiences and manage their emotional state. The subjective emotional state of a patient diagnosed with acute myocardial infarction is ignored. To study the emotional state, the authors developed a “Map of emotions of the route of a patient with acute myocardial infarction”. This map shows the palette of negative emotions of the patient and his accompanying relatives on the way from the sudden onset of symptoms to the arrival at the emergency department. The map shows their change to more positive emotions. At the prehospital stage, the medical staff of the ambulance should explain to the patient and his companion what is happening at each stage of the patient's journey. This will positively affect the transformation of negative emotions into positive ones, increase the patient's cognitive abilities.
Keywords: emotional state; emotions; acute myocardial infarction; patient route; prevention